Fazendo “sopa de carver”: a transtextualidade em Short cuts – cenas da vida, de Robert Altman - Soares, Bernardo Luiz Antunes (2019)
The present work intends to analyze the film adaptation Short cuts, by Robert Altman in relation to two of its source materials, the short story “So much water so close to home” and the poem “Lemonade”, by Raymond Carver. Through Gérard Genette’s transtextuality theory, the discussion was divided into five categories that contemplate distinct and complementary aspects of the relationship between the filmic text and the literary text. We discussed the use of music in cinema and the relations between poetry and music to reveal the expressiveness of music in the poem adaptation through theories by Michel Chion and Christina Cano; we also analyzed the editing role and the descentralized structure of the film to explore the narrative intersection, through the theories of Jacques Aumont and Jacques Derrida. Moreover, we analyzed the omnipresence of images in the (post-)modern society so as to deal with the sociology of adaptation, through the theory of Guy Debord; the transposition of characters and plot from the short story and the poem to the film with the aid of Linda Hutcheon; and the codes associated with realism employed in literary and filmic texts, through the theories of Roland Barthes, Roman Jakobson and André Bazin. All of those themes are directly associated with the theory of intertextuality, conceptualized by Julia Kristeva and further developed by other theoreticians. The results point to a work whose authors and distinct voices complement one another through elaborate techniques of adaptation, thus reaffirming adaptation as a powerful tool for the dialogue among arts.